Are children in public squares? an exploratory study on the use of playgrounds in urban squares - Alberto, Klaus Chaves (2024)
The availability and quantity of playgrounds within the cities can contribute for the population well-being by inactivating a diverse open public spaces usage. This study aims to identify relations between the presence of children, playground’s quantity and quality of Juiz de Fora’s (MG) playgrounds. All its public squares (n=95) were analyzed considering: the presence of users (considering their age group, gender, level of physical activity) and playground (considering their availability and quality of their Children Recreation Equipment - CRE). The results point out that only 60% of the squares have playgrounds with around 40% of the population living within 400m of those facilities. The public squares with playgrounds registered a broader number of children doing vigorous physical activities. Square available CRE’s quantity and quality were limited, nonetheless, when there were many and diversity there was also related with a higher level of physical activities. It is highlighted that only 43% of CREs were attending the evaluated safety requirements. The present study’s results point out the necessity of revision on public square’s planning and management to broad quantity, diversity, comfort and safety of their playgrounds.